Reduction of Waste of Time in Specimen Delivery Process in Health Industry Using Six Sigma Methodology - Nunthaphan Kanoksirirujisaya, Mohd Khairul Amri Kamarudin, Tepvisit Potikengrith; Kanitsorn Poonikom (International Journal of Advanced Science and Technology, 2020)
In numerous health industry Automated Guided Vehicles (AGVs) have been used in the process of medical specimen transport for a decade. Although they have completely used procedures of carefully design the environment and accommodation the methods to the automation, only a few studies have been investigated in the developing country. The purpose of this research seeks to reduce wasted time in the process of delivering specimens by foot in Thailand’s healthcare industry by using the Six Sigma methodology. Six Sigma consists of five phases: defining, measuring, analyzing, improving, and controlling, in conjunction with quality tools and Failure Mode and Effects Analysis (FMEA), which discovers potential causes of failures within the process; Risk Priority Number (RPN) is considered to identify causes associated with failures. The research was conducted in the Clinical Laboratory Section of Srinagarind Hospital. The average walking distance to deliver specimens was 416 meters/round. The average time spent walking to deliver specimens was 3.14 minutes/round. After improvements were made, which Found that the wasted time in transporting specimens decreased by 95 %. On average, an automated guided vehicle (AGV) was able to improve staff’s performance by 90%.